Crosslinguistic structural priming of passives in sentence comprehension: evidence from Chinese proficient EFL learners - Gong, Y (2023)
Crosslinguistic structural priming occurs when prior experience with a linguistic structure in one language facilitates the production and/or comprehension of similar structures in another language. This psycholinguistic phenomenon has been intensely investigated in bilinguals, but most research centres on the processes involved in language production. As such, crosslinguistic structural priming in language comprehension remains largely understudied, and there are considerable theoretical uncertainties over the mechanisms of bilingual structural representation and sentence processing during priming. Moreover, it is unclear how crosslinguistic priming interacts with language directions (L1 to L2 and L2 to L1). To address these gaps, this research project aims to examine and compare crosslinguistic structural priming effects across both language directions in Chinese EFL learners’ sentence comprehension, focusing on the passive constructions that pose learning challenges for Chinese-English bilinguals.